2021
DOI: 10.1002/lno.11765
|View full text |Cite
|
Sign up to set email alerts
|

Low diversity of a key phytoplankton group along the West Antarctic Peninsula

Abstract: The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
1
12
0
2
Order By: Relevance
“…At the Tara Oceans WAP sites, clade IV had much lower contributions than those of clade VII to TPG relative abundance. Finally, we found that, like our V9 18S ASV1, the dominant cryptophyte V4 18S ASV identified in a recent WAP study ( 19 ) had 100% nucleotide identity (to the V4 region) of our clade VII full-length sequence.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…At the Tara Oceans WAP sites, clade IV had much lower contributions than those of clade VII to TPG relative abundance. Finally, we found that, like our V9 18S ASV1, the dominant cryptophyte V4 18S ASV identified in a recent WAP study ( 19 ) had 100% nucleotide identity (to the V4 region) of our clade VII full-length sequence.…”
Section: Resultssupporting
confidence: 80%
“…We were able to compare the identified ASV and the V4 region of our full-length clade VII gene sequence and found they had 100% nucleotide identity. Hence, taking into account our integrative results and indications from prior studies of Ace Lake ( 40 ) and those of the nonfjord WAP transects ( 19 ), the novel TPG clade VII appears to be an important cryptophyte in multiple Antarctic regions, particularly in the WAP.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…While diatoms form blooms in both open ocean and coastal regions of the SO (Smetacek et al, 2012), high abundances of cryptophytes are mainly observed in coastal SO waters (Brown et al, 2021; Moline et al, 2004; Montes‐Hugo et al, 2009). In this study, we provide evidence that cryptophytes such as G. cryophila cannot cope well with low Fe concentrations, which are typical for open SO waters.…”
Section: Discussionmentioning
confidence: 99%